DIGITAL LESSON PLAN GENERATION AND ITS USEFULNESS FOR SECONDARY SCHOOL TEACHERS - Tan Choon Keong; Dg Norizah Kiflee, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The Ministry of Education (MOE) Malaysia directed that every teacher of secondary schools is responsible to prepare lesson plan for each lesson when teaching in a class. The paper reports the use of a prototype system by school teachers to produce digital lesson plans. The system was developed utilising the ADDIE Model. Five teachers from Kian Kok High School, Kota Kinabalu, Sabah was selected to test-run the system. They were also observed for teaching using the digital lesson plan. The results of the interview were analysed in a qualitative way. The findings showed that all the five respondents agreed the system was able to function smoothly to create digital lesson plan. Many other functions were tested and also reported to be successful. The result of the teaching observation also proved that the digital lesson plan is useful for the teachers and also able to maintain lesson plan standard fixed by the MOE. Many challenges were reported by the respondents but the researcher was only managed to attend to some of them only due to financial constraints of the grant. The research concluded that lesson plans generator that is reliable and effective must be in the online mode in a future so that users can be engaged online for more teaching resources.